Pengaruh Sikap Siswa dan Pemahaman Konsep Ekosistem Terhadap Kepedulian Lingkungan - Nur Rizkiyah (Peneliti.net, 2019)
This study aims to determine and analyze the influence of student attitudes on Biology lessons and understanding concepts towards environmental awareness of State High School students in Jagakarsa District, South Jakarta. This type of research is associative descriptive. The population of this study was all students of class X in Natural Sciences at the State High School in Jagakarsa District, South Jakarta 885 students. Sampling with proportional random sampling obtained a sample of 90 students. The data analysis technique is the path analysis approach. The results showed that students' attitudes directly did not have a significant effect on environmental awareness. However, indirectly through the variable understanding of ecosystem concepts has a significant effect on environmental awareness. Furthermore, understanding the concept of ecosystem has a significant effect on environmental awareness. Overall, the magnitude of the indirect effect of students' attitudes towards environmental awareness through understanding the concept of the ecosystem is 47.4%. While the remaining 52.6% is contributed by other factors not examined in this study.